Makna Strategi dan Praktik Keluarga dalam Penguatan Nilai Spiritual Remaja Penghayat Kepercayaan terhadap Tuhan Yang Maha Esa: Studi Fenomenologis - Parida Parida; Wilodati Wilodati; Mirna Nu Alia Abdullah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study is motivated by the important role of the family in maintaining and strengthening spiritual values among adolescents of belief communities amid the currents of modernization and social marginalization. The purpose of this research is to understand the meaning of family strategies in reinforcing spiritual values among adolescents who adhere to belief systems in God Almighty. This study employs a qualitative approach with a phenomenological design to explore the lived experiences of participants in depth. Data were collected through in-depth interviews, observation, and documentation involving families from belief communities. The findings reveal that family strategies are implemented through habituation, role modeling, open communication, and value protection, which are interpreted as conscious efforts to maintain adolescents’ spiritual identity. Spiritual values are transmitted not only verbally but also through daily practices directly experienced by adolescents. The implications of this study emphasize that families play a central role as primary agents of socialization in shaping adolescents’ spiritual resilience, particularly within minority contexts, thus highlighting the need to strengthen the role of families in addressing evolving socio-cultural challenges.